1994
DOI: 10.1007/bf00004360
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and clearance of exogenous estradiol-17β and testosterone during the early development of coho salmon (Oncorhynchus kisutch), including eggs, alevins and fry

Abstract: The uptake and clearance of estradiol-17β (E2) and testosterone (T) were examined during the initial stages of development of coho salmon (Oncorhynchus kisutch), including eyed-eggs, newly hatched alevins and first feeding fry. Radiolabeled steroids were administered through the water in tracer amounts with or without their nonradioactive form at 400 μg l(-1). Regardless of developmental stage, saturation levels were invariably attained earlier for T than for E2, thus resulting in a higher incorporation of E2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 30 publications
0
19
1
1
Order By: Relevance
“…This conversion may explain the rapid decrease in yolk hormone levels within the first days of incubation reported in previous studies (Bowden et al, 2002;Eising et al, 2003;Elf and Fivizzani, 2002). Steroid metabolism by the embryo and the extraembryonic membranes (yolk sac, allantois, amnion, chorion) has been observed in all species studied so far, in fish (Antila, 1984;Piferrer and Donaldson, 1994), amphibians (Antila, 1977), reptiles (Painter and Moore, 2005;Paitz and Bowden, 2008), birds Parsons, 1970) and mammals (Levitz, 1966). Chick blastoderm can metabolise steroid hormones in vitro even within the first 2 days after laying Parsons, 1970), producing both conjugated and free steroids.…”
Section: Polar and Apolar Metabolitesmentioning
confidence: 69%
“…This conversion may explain the rapid decrease in yolk hormone levels within the first days of incubation reported in previous studies (Bowden et al, 2002;Eising et al, 2003;Elf and Fivizzani, 2002). Steroid metabolism by the embryo and the extraembryonic membranes (yolk sac, allantois, amnion, chorion) has been observed in all species studied so far, in fish (Antila, 1984;Piferrer and Donaldson, 1994), amphibians (Antila, 1977), reptiles (Painter and Moore, 2005;Paitz and Bowden, 2008), birds Parsons, 1970) and mammals (Levitz, 1966). Chick blastoderm can metabolise steroid hormones in vitro even within the first 2 days after laying Parsons, 1970), producing both conjugated and free steroids.…”
Section: Polar and Apolar Metabolitesmentioning
confidence: 69%
“…A possible interpretation is that high ERα expression in progeny of NBH is due to exposure to estrogenic NBH contaminants accumulated in yolk, as previously observed in embryos derived from fish exposed to steroids (Piferrer and Donaldson, 1994; Yeoh et al, 1996). If so, this implies that the ERα autoregulatory loop is operative, and would be predicted to lead to increased expression of other ERα gene targets.…”
Section: Introductionmentioning
confidence: 81%
“…Kime et al (1992) noticed significant uptake of radioactive steroids by goldfish ovarian tissue, and Kime and Abdullah (1994) found that, as in the present study, the amount which was taken up was increased, rather than decreased, by the addition of cold steroid. Piferrer and Donaldson (1994) showed that fertilized eggs and alevins of coho salmon were able to take up exogenous testosterone and 17f3-estradiol, and suggested that it was the yolk which was responsible for absorbing the steroids. This is in agreement with the results of the present study which showed that yolkextruded follicles do not take up label.…”
Section: Discussionmentioning
confidence: 98%